2022
DOI: 10.18087/cardio.2022.8.n2147
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of right ventricular functions in acromegaly: comparison of active disease with remission

Abstract: Aim    Cardiac involvement in acromegaly is defined as acromegalic cardiomyopathy, an insidious and chronic disease. Previous research on acromegalic cardiomyopathy was largely focused on morphological and functional assessment of the left heart. Since the literature data regarding right heart function in acromegalic patients are limited, we aimed to evaluate the structure and function of the right heart in such patients.Material and Methods    We included 43 adult participants as the acromegaly group and 42 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Increased RA minor diameter could be detected in acromegaly, which correlated with hGH and IGF-1 levels [93]. Profound RA remodeling could be demonstrated, including RA dilation in all phases of RA function without changes in any RA-SV and RA-EmF values, especially in acromegaly patients with active disease in the MAGYAR-Path Study.…”
Section: In Acromegalymentioning
confidence: 86%
See 1 more Smart Citation
“…Increased RA minor diameter could be detected in acromegaly, which correlated with hGH and IGF-1 levels [93]. Profound RA remodeling could be demonstrated, including RA dilation in all phases of RA function without changes in any RA-SV and RA-EmF values, especially in acromegaly patients with active disease in the MAGYAR-Path Study.…”
Section: In Acromegalymentioning
confidence: 86%
“…hGH and IGF-1 positively correlated with RV longitudinal diameter and indexed RV end-diastolic area. Patients with active acromegaly had increased RV index of myocardial performance, isovolumetric contraction time, and shortened RV ejection time compared to patients in remission [93]. In another study, increased deceleration time and decreased E/A were found [94].…”
Section: In Acromegalymentioning
confidence: 89%